1999
DOI: 10.1007/s004220050521
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of goal-directed rhythmical aiming

Abstract: Based on the kinematics of goal-directed aiming movements in a reciprocal Fitts' task, a minimal limit cycle model is proposed that is capable of producing the behavior observed at levels of task difficulty ranging from 3 to 7. From graphical and statistical analyses of the phase planes, Hooke's planes and velocity profiles, we concluded that the minimal terms to be included in the model were (i) a nonlinear damping in the form of a self-sustaining, velocity-driven Rayleigh oscillator and (ii) a nonlinear stif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
172
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(184 citation statements)
references
References 29 publications
10
172
2
Order By: Relevance
“…Second, the trajectory choice may differ between precision conditions. Mottet and Bootsma (1999) showed that, with increased precision demands, systematic changes in kinematics occur; most notably movement speed increases in the middle part of the movement and decreases near the target. In other words, higher precision demands lead to higher accelerations in the first part of the movement and higher decelerations in the second part, where the actual precision is required.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the trajectory choice may differ between precision conditions. Mottet and Bootsma (1999) showed that, with increased precision demands, systematic changes in kinematics occur; most notably movement speed increases in the middle part of the movement and decreases near the target. In other words, higher precision demands lead to higher accelerations in the first part of the movement and higher decelerations in the second part, where the actual precision is required.…”
Section: Discussionmentioning
confidence: 99%
“…An advantage of this manipulation is that, by varying the stringency of the two required subtasks, graded variations in the degree of attentional asymmetry may be induced. However, a considerable disadvantage is that the associated spatial demands may alter the limb's component dynamics [e.g., influencing the (non-linear) stiffness of the component oscillator, see Mottet & Bootsma, 1999]. Theoretically, such differences in component dynamics may affect the relative phase dynamics as well (Daffertshofer, Van Den Berg, & Beek, 1999;Fuchs, Jirsa, Haken, & Kelso, 1996).…”
Section: Experimental Manipulations and Predictionsmentioning
confidence: 99%
“…The first hypothesis proposes that discrete movements are fundamental, whereas rhythmic movements are mere concatenations of discrete movements (Feldman, 1980;Shadmehr and Wise, 2005). In contrast, the second hypothesis states that rhythmic movements are fundamental, whereas discrete movements are truncated rhythmic movements (Schöner, 1990;Mottet and Bootsma, 1999). The third hypothesis assumes that rhythmic and discrete movements are two different (or partially different) classes of movements (Sternad et al, 2000;Buchanan et al, 2003).…”
Section: Introductionmentioning
confidence: 99%